Th 17 Cells: Role in Inflammation and Autoimmune Disease - Quesniaux, Valérie; Ryffel, Bernhard; Di Padova, Franco (Progress in Inflammation Research, 2009)
With the recent definition of the Th17 cell subset, a new paradigm in innate and adaptive immunity has been established. This book describes the function of the Th17 cell subset and its prevalent role in many inflammatory and autoimmune diseases. The mechanism by which this T cell subset is generated and maintained shows specific differences between mice and man which are reviewed. One characteristic of Th17 cells is to secrete specific and unique cytokines such as IL-17A, IL-17F and IL-22; their functions are described in detail. These cytokines have acquired a prevalent role in many pathological conditions in animal models and in humans. Targeting these cytokines as well as the generation of Th17 cells may open new ways to treat many autoimmune diseases. The role of Th17 in infectious conditions is also addressed.